The Japanese consumer an alternative economic history of modern Japan - Francks, Penelope 1949- (Cambridge, [Englnad] Cambridge University Press, 2009)
"By the late twentieth century, Japanese people were renowned as the world's most avid and knowledgeable consumers of fashion, luxury and quality, while the goods that embodied their tastes and lifestyle were becoming a part of global culture. Penelope Francks' book offers an alternative account of Japan's modern economic history from the perspective of the consumer. Tracing Japan's economy from the eighteenth century to the present, she shows how history has conditioned what Japanese people consume and compares their experiences with those of Europe and North America. In so doing the author presents a lucid and informed account of everyday life in Japan, exploring what people eat, how they dress, the household goods they acquire, and their preferred shopping and leisure activities. This beautifully illustrated book succeeds in making economic history palatable and entertaining. It will be a treat for students and all those interested in Japanese society and culture"--Provided by publisher.
Keywords: Consumption (Economics) -- Japan -- History; Consumers -- Japan -- History